Role of Justice Principle in Good Governance to Develop the Performance of Employees in Institutions (An analytical study on a sample of employees at Naval Academy): Role of Justice Principle in Good Governance to Develop the Performance of Employees in Institutions (An analytical study on a sample of employees at Naval Academy) - Ali, Ahmed; Saleh, Rasha (The Gulf Economist, 2023)
This study aims to express the role of justice and the extent of its contribution to the development of human resources and the improvement of their job performance. The study conducted for a sample of workers in the Arabian Gulf Academy for Marine Studies. As a hypothesis scheme was built according to the variables of the current study, and on this basis the main and sub-hypotheses were developed. The questionnaire was used in the process of collecting data from a community of (180) employees working in the Maritime Academy. The results of the study showed that there is a positive effect for the role of justice in good governance and the development of human resources.